2017
DOI: 10.1021/acs.jpcc.7b02939
|View full text |Cite
|
Sign up to set email alerts
|

Extended Space Charge Region and Unoccupied Molecular Band Formation in Epitaxial Tetrafluorotetracyanoquinodimethane Films

Abstract: Generating well-defined molecular structures at inorganic/organic interfaces and within molecular films is fundamental for charge carrier transport and thus the performance of organic molecule-based (opto)­electronic devices. Here we show by means of low-energy electron diffraction that tetrafluorotetracyano­quinodimethane (F4TCNQ) grows in an epitaxial fashion on the Au(111) surface, resulting in a unit cell which consists of one molecule. In this well-ordered crystalline films we found the formation of an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
(75 reference statements)
2
17
0
Order By: Relevance
“…Deposition of F 4 TCNQ onto the Au(111) surface held at room temperature, from an organic molecular beam deposition source, led to the formation of the ordered phase previously identified by STM 1 and LEED. 27 Figure 1 a shows the resulting LEED pattern, obtained using a low incident current multichannel-plate amplified optics (MCP-LEED). Due to the low symmetry of the unit mesh of this phase, the pattern is a sum of the patterns from multiple domains related by the rotational and mirror symmetry elements of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Deposition of F 4 TCNQ onto the Au(111) surface held at room temperature, from an organic molecular beam deposition source, led to the formation of the ordered phase previously identified by STM 1 and LEED. 27 Figure 1 a shows the resulting LEED pattern, obtained using a low incident current multichannel-plate amplified optics (MCP-LEED). Due to the low symmetry of the unit mesh of this phase, the pattern is a sum of the patterns from multiple domains related by the rotational and mirror symmetry elements of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of TCNQ and F4-TCNQ on different metal surfaces has been the subject of many different experimental and theoretical studies. ,, From the early results, it was clear that both molecules adsorb flat on most metal surfaces, accepting negative charge from the substrate and causing an increase in the work function of the system. Maybe the only exception is the adsorption of TCNQ on the Au(111) surface.…”
Section: Introductionmentioning
confidence: 99%
“…To study the role of adatoms, we chose F4TCNQ on Au(111), since multiple independent studies have found that it readily and reproducibly forms well-ordered structures containing adatoms as part of the adlayer. 35 , 44 , 46 , 47 The surface structure consists of only one F4TCNQ molecule and one adatom per unit cell, which reduces the computational effort and facilitates the analysis of this system (compared to larger unit cells). The strong interactions between the adsorbate and substrate lifts the herringbone reconstruction of Au(111), and the F4TCNQ molecule-Au-adatom network is arranged in a Au(111) surface supercell, as shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%